2021
DOI: 10.21776/ub.afssaae.2021.004.01.6
|View full text |Cite
|
Sign up to set email alerts
|

Identifying elements of mushroom business development in Malang City with a Canvas model approach

Abstract: The mushroom agroindustry has a profitable business opportunity for farmers because it is easy to cultivate, needs short planting time, and does not require extensive planting land. Moreover, the price of post-harvest products is quite high. To face increasingly intense competition, mushroom agroindustry actors need to implement strategic management to increase business competitiveness. The purposes of this study are to identify a business model using the business mode canvas (BMC) approach, analyse the intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
2

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
3
0
2
Order By: Relevance
“…And the farmers can realize their higher returns if they are made proficient in social media as they can utilize social media for marketing of their produce. The use of social media for SMEs facilitates business development, increases product sales, eases communication with consumers, and develops and expands market networks was also suggested by Filipov (2021) & Citraresmi et al, (2021.…”
Section: W-t Strategiesmentioning
confidence: 93%
See 2 more Smart Citations
“…And the farmers can realize their higher returns if they are made proficient in social media as they can utilize social media for marketing of their produce. The use of social media for SMEs facilitates business development, increases product sales, eases communication with consumers, and develops and expands market networks was also suggested by Filipov (2021) & Citraresmi et al, (2021.…”
Section: W-t Strategiesmentioning
confidence: 93%
“…Shirur & Chandregowda (2017) had similar finding for opportunities i.e., increasing awareness among people leading to increasing demand for mushrooms in the market". Citraresmi et al, (2021) also reported for opportunities, "optimizing the online market" and threat was "competitor from other food sources".…”
Section: Internal Factor Evaluation Matrix (Ifem)mentioning
confidence: 99%
See 1 more Smart Citation
“…Bahkan kini peluang tersebut semakin terbuka dengan adanya pemasaran melalui media online, walaupun telah bermunculan berbagai varian kuliner yang menjadi pesaing akan makanan sehat ini. (Citraresmi et al, 2021). Untuk itu, diperlukan beberapa strategi untuk peningkatan budi daya jamur tiram ini, antara lain melalui inovasi produk dan peningkatan kualitas produk, peningkatan/ perluasan cakupan pemasaran serta penjalinan kerjasama dengan berbagai mitra atau stakeholder (pemangku kepentingan) terkait (Al Ridho et al, 2020;Citraresmi et al, 2021;Rachmawati et al, 2022).…”
unclassified
“…(Citraresmi et al, 2021). Untuk itu, diperlukan beberapa strategi untuk peningkatan budi daya jamur tiram ini, antara lain melalui inovasi produk dan peningkatan kualitas produk, peningkatan/ perluasan cakupan pemasaran serta penjalinan kerjasama dengan berbagai mitra atau stakeholder (pemangku kepentingan) terkait (Al Ridho et al, 2020;Citraresmi et al, 2021;Rachmawati et al, 2022). Hasil penelitian tersebut di atas menggambarkan budi daya jamur tiram dikembangkan dari sisi peningkatan usahanya, tetapi cenderung belum menonjolkan bagaimana proses pemberdayaan bagi mereka yang terlibat.…”
unclassified